Candy Advertising, Consumption and Childhood Happiness (Argentina, 1930-1943) - Scheinkman, Ludmila (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2018)
This article explores advertising images produced by the candy and confectionery industries, which disseminated, created, and modified on a massive scale social roles and constructions of childhood in Argentina in the 1930s. In this analysis, we point out a significant transformation in the arguments and appeals used by publicity directed to children: the emergence of a decisive link between childhood and happiness, which became dominant in this decade. This happiness would be attained, according to the advertisers, by consuming these goods, which in addition to pleasure provided games and entertainment to cheer up children, and promised happy childhoods